Reirradiation in progressive high-grade gliomas: Outcome, role of concurrent chemotherapy, prognostic factors and validation of a new prognostic score with an independent patient cohort - Scholtyssek, Felix; Zwiener, Isabella; Schlamann, Annika; Seidel, Clemens; Meixensberger, Juergen; Bauer, Manfred; Hoffmann, Karl-Titus; Combs, Stephanie E.; Von Bueren, Andre O.; Kortmann, Rolf-Dieter; Mueller, Klaus (Radiation Oncology, 2013)
Purposes: First, to evaluate outcome, the benefit of concurrent chemotherapy and prognostic factors in a cohort of sixty-four high-grade glioma patients who underwent a second course of radiation therapy at progression. Second, to validate a new prognostic score for overall survival after reirradiation of progressive gliomas with an independent patient cohort.Patients and methods: All patients underwent fractionated reirradiation with a median physical dose of 36 Gy. Median planned target volume was 110.4 ml. Thirty-six patients received concurrent chemotherapy consisting in 24/36 cases (67%) of carboplatin and etoposide and in 12/36 cases (33%) of temozolomide. We used the Kaplan Meier method, log rank test and proportional hazards regression analysis for statistical assessment.Results: Median overall survival from the start of reirradiation was 7.7 ± 0.7 months. Overall survival rates at 6 and 12 months were 60 ± 6% and 24 ± 6%, respectively. Despite relatively large target volumes we did not observe any major acute toxicity. Concurrent chemotherapy did not appear to improve outcome. In contrast, female gender, young age, WHO grade III histology, favorable Karnofsky performance score and complete resection of the tumor prior to reirradiation were identified as positive prognostic factors for overall survival. We finally validated a recent suggestion for a prognostic score with our independent but small patient cohort. Our preliminary findings suggest that its ability to discriminate between different prognostic groups is limited.Conclusions: Outcome of our patients was comparable to previous studies. Even in case of large target volumes reirradiation seems to be feasible without observing major toxicity. The benefit of concurrent chemotherapy is still elusive. A reassessment of the prognostic score, tested in this study, using a larger patient cohort is needed. © 2013 Scholtyssek et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2023-03-08